Observation of surface optical phonons on SrTiO3(100) - Baden, A; Cox, P; Egdell, R; Orchard, A; Willmer, R (1981)
Surface optical phonons on the (100) face of strontium titanate have been observed by high-resolution EELS. Good agreement is found between experimental spectra and predictions based on a semi-classical theory, using the known dielectric function of strontium titanate.